Propuesta de sistema de gestión por procesos para la asociación de mujeres comunitarias del cantón Tosagua - Jiménez Navarrete, Danixa Ramona (2023)
This research work focuses on proposing a process management system for the Association of Community Women of the Tosagua canton. Taking into account that nowadays associations have been developing and at the same time have reformed their internal management, with this objective three specific phases were developed, initially the characterization of the association was carried out through an assembly with the members, which allowed us to know the current situation of the company, to obtain this information about the processes, a field survey was carried out through an interview with the people who manage the processes and work in the entity, confirming the processes, activities and occupations that they perform in an empirical way; with these data we proceeded to identify the processes and procedures of AMUCOMT, then using the ANSI symbology we obtained the flowcharts allowing a feasible analysis showing the sequences of activities that occur in each process, afterwards, the process management manual was realized, taking into consideration the current Popular and Solidarity Economy (EPS) standards, and finally, conclusions and recommendations were done, concluding that the manual is a necessary tool that will allow members to follow a sequential order in the activities they are in charge of, and that it will also favor and optimize the use of resources in the organization.